Adaptation to acute pulmonary hypertension in pigs. Issue 5 (7th March 2018) - Mechelinck, Mare; Hein, Marc; Bellen, Sven; Rossaint, Rolf; Roehl, Anna B.
Abstract: The extent of right ventricular compensation compared to the left ventricle is restricted and varies among individuals, which makes it difficult to define. While establishing a model of acute pulmonary hypertension in pigs we observed two different kinds of compensation in our animals. Looking deeper into the hemodynamic data we tried to delineate why some animals could compensate and others could not. Pulmonary hypertension (mean pressure 45 mmHg) was induced gradually by infusion of a stable thromboxane A2 analogue U46619 in a porcine model ( n = 22). Hemodynamic data (pressure‐volume loops, strain‐analysis of echocardiographic data and coronary flow measurements) were evaluated retrospectively for the short‐term right ventricular compensatory mechanisms and limits (Roehl et al. [2012] Acta Anaesthesiol. Scand., 56:449–58) 10 animals showed stable arterial blood pressures, whereas 12 pigs exhibited a significant drop of 16.4 ± 9.9 mmHg. Cardiac output and heart rate were comparable in both groups. In contrast, right ventricular contractility and coronary flow only rose in the stable group. The unchanging values in the decrease group correlated with an increasing ST‐segment depression and a loss of ventricular synchronism and resulted in a larger septum bulging to the right ventricle. Simultaneously, a reduced left‐ventricular end‐diastolic volume and a missing improvement in contractility in the posterior septal and inferior free wall of the left ventricle have been observed. Our findings suggest that right ventricular compensation during acute pulmonary hypertension is strongly dependent on the individual capability to increase coronary flow. The cause for inter‐individual variability could be the dimension and reactivity of the coronary system. Abstract : Two different types of adaptation to stepwise induced acute pulmonary hypertension in pigs were observed: Some animals were able to adapt, whereas others were not and showed first signs of right heart failure. Furthermore hemodynamic analyses were conducted. The findings suggest that right ventricular compensation during acute pulmonary hypertension is strongly dependent on the individual dimension and reactivity of the coronary system.